2014
DOI: 10.1186/1471-2458-14-800
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with stunting among children of age 24 to 59 months in Meskan district, Gurage Zone, South Ethiopia: a case-control study

Abstract: BackgroundStunting is one of the major causes of morbidity among under-five children Knowledge about risk factors of stunting is an important precondition for developing and strengthening nutritional intervention strategies. The purpose of this study was to assess factors associated with stunting among children of age 24 to 59 months in Meskan District of Gurage Zone, South Ethiopia.MethodsCommunity based case-control study was conducted among children of age 24 to 59 months. A multistage sampling technique wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
94
6
47

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(202 citation statements)
references
References 18 publications
32
94
6
47
Order By: Relevance
“…The odds of stunting were significantly higher in male children than female counterparts which are consistent with previous studies [9][10][11][12][13][14][15][16][17][18][19][20][21]. This may be attributed to diseased status during the study period.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The odds of stunting were significantly higher in male children than female counterparts which are consistent with previous studies [9][10][11][12][13][14][15][16][17][18][19][20][21]. This may be attributed to diseased status during the study period.…”
Section: Discussionsupporting
confidence: 82%
“…In addition previous local studies mainly try to show the association between socioeconomic and demographic factors such as family income/wealth status/, farm land, education status, family size, child's age and gender [11][12][13][14][15][16][17][18] with chronic under nutrition through cross sectional survey. Only few studies were reported about the association between chronic undernutrition and risk factors like Infant and Young Child Feeding (IYCF) practices which includes pre-lacteal feeding [12,14], time of initiation of breast feeding [5], feeding of colostrum [12], duration of exclusive breast feeding [5,18], duration of breast feeding [5,14], age at complementary feeding [5,14], the type and fre quency of complementary foods [14] and methods of complementary feeding [12,14,17]as well as environmental health state like water supply, sanitation and housing conditions [11,12,15,16]. However, most of these surveys were conducted on insufficient number of study participants and used cross sectional study designs which are not appropriate to identify risk factors of chronic under nutrition (stunting).…”
Section: Introductionmentioning
confidence: 99%
“…The present study is in agreement with previous studies stating that children who were breastfed for less than 24 months were more at risk for stunting, as compared to children who were breastfed for at least 24 months. (16,17) However, the present study is not in line with the study by Kamal which showed that breastfeeding for less than 24 months is not a risk factor for the prevalence of stunting. (18) Weaning is a term used to refer to the transition period in which infants still receive liquid food, either breast milk or formula milk, but are also gradually introduced to solid food.…”
Section: Discussioncontrasting
confidence: 57%
“…This study is similar to a study in Ethiopia which showed that children with less than 6 months of breastfeeding had a greater risk of stunting than children with exclusive breastfeeding during the first 6 months. (24) A study in Nepal showed that children who did not receive colostrum had a 3.40 times greater risk of stunting. (13) Low birth weight infants tend to have intrauterine growth retardation because of poor maternal nutrition.…”
Section: Discussionmentioning
confidence: 99%